Artificial Intelligence in Higher Education: Lessons from Chile and Mexico - Barrera, Alejandra Gaitan; Azeez, Govand Khalid (International Higher Education, 2025)
Artificial intelligence is transforming higher education in Latin America, with Chile and Mexico leading in AI design and implementation. This article examines pioneering AI initiatives at two universities: the Pontifical Catholic University of Chile, and the Monterrey Institute of Technology and Higher Education. Their experiences offer valuable insights and frameworks for AI integration in higher education across the Global South and emerging economies.